Effect of position and exercise on measurement of muscle quantity and quality: towards a standardised pragmatic protocol for clinical practice - Carly Welch; Zeinab Majid; Isabelle Andrews; Zaki Hassan-Smith; Vicky Kamwa; Hannah Picton; Daisy Wilson; Thomas A. Jackson (BMC, 2021)
Abstract Background Ultrasonography is an emerging non-invasive bedside tool for muscle quantity/quality assessment; Bioelectrical Impedance Analysis (BIA) is an alternative non-invasive bedside measure of body composition, recommended for evaluation of sarcopenia in clinical practice. We set out to assess impact of position and exercise upon measures towards protocol standardisation. Methods Healthy volunteers aged 18-35 were recruited. Bilateral Anterior Thigh Thickness (BATT; rectus femoris and vastus intermedius), BATT: Subcutaneous Ratio (BATT:SCR), and rectus femoris echogenicity were measured using ultrasound and BIA was performed; 1) lying with upper body at 45° (Reclined), 2) lying fully supine at 180o (Supine), 3) sat in a chair with upper body at 90o (Sitting), and 4) after exercise Reclined. Variability of Skeletal Muscle Mass (SMM) by two different equations from BIA (SMM-Janssen, SMM-Sergi), phase angle, fat percentage, and total body (TBW), extracellular (ECW), and intracellular water (ICW) were assessed. Results Forty-four participants (52% female; mean 25.7 years-old (SD 5.0)) were recruited. BATT increased from Reclined to Sitting (+ 1.45 cm, 1.27-1.63), and after exercise (+ 0.51, 0.29-0.73). Echogenicity reduced from Reclined to Sitting (− 2.1, − 3.9 - -0.26). SMM-Sergi declined from Reclined to Supine (− 0.65 kg, − 1.08 - − 0.23) and after exercise (− 0.70 kg, − 1.27 - -0.14). ECW increased from Reclined to Sitting (+ 1.19 L, 0.04-2.35). There were no other statistically significant changes. Conclusion Standardisation of protocols is especially important for assessment of muscle quantity by ultrasonography; BIA measurements may also vary dependent on the equations used. Where possible, participants should be rested prior to muscle ultrasonography and BIA, and flexion of the knees should be avoided.